Adult orthodontics - Melsen, Birte (Wiley-Blackwell, 2012)
"This book addresses the increasing prominence of adult orthodontics and provides an authoritative resource on the subject. The opening chapters provide the context for adult orthodontics, including patient demographics and etiology. The middle section of the book details treatment planning considerations and approaches. The final part of the book profiles patient cases, suggesting initial outcomes and longer term expectations. This book will be of value to all those providing adult orthodontic services and those dealing with orthodontics as part of the inter-disciplinary management of the adult dentition"--Provided by publisher